Heritable Thrombophilia in Venous Thromboembolism in Northern Pakistan: A Cross-Sectional Study - Maria Khan (Hindawi Limited, 2021)
Background. Venous thromboembolism (VTE) is referred to as formation of clots in a deep vein or lodging of thrombus towards the lungs which could be fatal yet preventable. The risk of developing VTE can be increased by various factors. Where there are innumerable acquired causes, the possibility of inherited thrombophilia cannot be ignored. In view of this, we have evaluated all patients with venous thromboembolism for inherited thrombophilia. Objective. To evaluate the frequencies of antithrombin (AT) deficiency, protein C and S deficiencies, Factor V Leiden, and prothrombin gene mutations in patients harboring venous thromboembolism. Materials and Methods. A study comprising of 880 patients who were presented with manifestations of venous thromboembolism was conducted from July 2016 to June 2017. A blood sample collected from patients was screened for thrombophilia defects encompassing AT, protein C and S deficiencies, Factor V Leiden, and prothrombin gene mutations. All acquired causes of thrombosis were excluded. Results. Of 880 patients who underwent screening for thrombophilia, 182 patients demonstrated VTE history. Their age ranged from 1 to 58 years. Males constituted a predominant group. About 45 (24.7%) patients had evidence of heritable thrombophilia. Of these, 20 (10.9%) had AT deficiency, 9 (4.9%) had Factor V Leiden mutation, 6 (3.2%) had protein C deficiency, whereas protein S deficiency and prothrombin gene mutation both were found in 5 (2.7%) patients. Conclusion. Our study illustrated the highest frequency of antithrombin deficiency among other investigated thrombophilia defects.